1998
DOI: 10.1007/s001340050718
|View full text |Cite
|
Sign up to set email alerts
|

Weaning from mechanical ventilation in pediatric intensive care patients

Abstract: Three-quarters of ventilated children can be successfully weaned after a trial of spontaneous breathing lasting 2 h. Both tidal volume and frequency-to-tidal volume ratio indexed to body weight were poor predictors of weaning failure in the study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 21 publications
(23 reference statements)
2
52
0
13
Order By: Relevance
“…Using 5 cm H 2 O CPAP rather than no pressure support during the measurements may have affected the performance of the RSB index (26) as values are higher during unassisted breathing than with pressure support (26). In children, however, when RSB was assessed without pressure support, the area under the ROC curve was only 0.57 (9). The broad age range and hence respiratory rates encountered in the pediatric population may make the RSB index inappropriate as a predictor of extubation outcome in that setting (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using 5 cm H 2 O CPAP rather than no pressure support during the measurements may have affected the performance of the RSB index (26) as values are higher during unassisted breathing than with pressure support (26). In children, however, when RSB was assessed without pressure support, the area under the ROC curve was only 0.57 (9). The broad age range and hence respiratory rates encountered in the pediatric population may make the RSB index inappropriate as a predictor of extubation outcome in that setting (8).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of multivariate indices in children, such as the rapid-shallow breathing index (RSB) (respiratory rate [RR] divided by tidal volume [VT]) (5) and the CROP index (compliance, RR, oxygenation, and inspiratory pressure [PI]), however, have been limited and yielded contradictory results. We (7) and others (8,9) have shown that the predictive power of those indices in children is poor, whereas Baumeister and colleagues (10), demonstrated that the CROP index discriminated strongly between successful and unsuccessful extubation.…”
mentioning
confidence: 86%
“…It is suggested that nurses and allied health professionals tend to adhere to protocols more readily as a result of their different training and professional cultures (Lawton and Parker, 1999) and, indeed, the majority of studies evaluating the efficacy of weaning protocols have focused on comparing nurse or respiratory therapist (RT) led weaning using protocols with traditional doctor-led practice. The evidence is fairly evenly divided in both the adult and paediatric literature: some studies demonstrated more effective patient outcomes with protocolisedweaning (Ely et al, 1996;Farias et al, 1998;Grap et al, 2003;Horst et al, 1998;Kollef et al, 1997;Scheinhorn et al, 2001) and a similar number demonstrated no significant difference in outcomes Burns et al, 1998;Djunaedi et al, 1997;Keogh et al, 2003;Krishnan et al, 2004;Randolph et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…6 Bousso et al remark that the difference in results could be reflecting the presence of populations with dissimilar characteristics. This is a common situation when analyzing studies conducted in South America, where there is a predominance of primary respiratory diseases 1,5,[8][9][10]14 compared to the United States or Europe, with predominance of elective surgical patients. 4,6,11,15 At this time, there still are no reliable criteria to predict which patients will require reintubation after tolerating a spontaneous breathing trial.…”
mentioning
confidence: 99%